Serum cardiac troponin I concentrations in ewes diagnosed with parturient paresis: correlation with blood ionized calcium and conventional cardiac enzymes - Tumer, Kenan Cagri; Caliskan, Mehmet; Safak, Tarik (Sivar-Soc Italiana Veterinari Animali Reddito, 2021)
Calcium is an essential mineral for cardiac muscle excitation-contraction coupling and relaxation, and hypocalcemia results in a decrease in myocardial contractility force and an increase in cardiac cell permeability. Therefore, myocardial damage can occur in ewes with parturient paresis, a metabolic disease caused by decreased blood ionized calcium (iCa) concentrations. This study aimed to investigate the occurrence of myocardial damage in ewes diagnosed with parturient paresis by measuring serum cardiac troponin I (cTnI) concentrations as well as to determine whether a correlation exists among cTnI, iCa, and conventional enzymes, namely, myocardial band of creatine kinase (CK-MB), creatine kinase (CK), aspartate aminotransferase (AST), and lactate dehydrogenase (LDH). Twelve ewes diagnosed with parturient paresis (iCa 1.0 mmol/L) and ten healthy control ewes (iCa >= 1 mmol/L) were used in this study. To analyze the blood iCa, beta-hydroxybutyrate (beta-OHB), and serum cTnI, CK-MB, CK, AST, and LDH concentrations, we collected venous blood samples from the vena jugularis of the ewes. Serum cTnI concentrations were significantly increased in the patient group (1.11 +/- 0.62 ng/mL) compared with those in the control group (0.02 +/- 0.01 ng/mL). The serum concentrations of CK-MB, CK, AST, and LDH were also higher in the patient group than in the control group. Moreover, cTnI was positively correlated with AST (r = 0.639; P = 0.001), LDH (r = 0.553; P = 0.008), and CK (r = 0.598; P = 0.003). However, a significant negative correlation was detected between cTnI and iCa (r = -0.867; P = 0.001). The results showed that myocardial damage occurred in ewes with parturient paresis.
Keywords: Cardiac troponin I; ewe; ionized hypocalcemia; parturient paresis